Impact of resistance training intensity on body composition and nutritional intake among college women with overweight and obesity: a cluster randomized controlled trial - Wang, Qiang; Xiao, Wen Sheng; Danaee, Mahmoud; Geok, Soh Kim; Gan, Wan Ying; Zhu, Wang Li; Mai, Yi Qiang (Frontiers in Public Health, 2025)
IntroductionThe prevalence of overweight and obesity among college women is a public health concern. This study examined the effects of different intensities of resistance training on body composition and nutritional intake in overweight and obese college women.MethodsA cluster-randomized controlled trial with a 12-week intervention included 72 participants, divided into low, moderate, and high-intensity resistance training groups, along with a control group. The 3-day food record and other standardized instruments measured the corresponding variables.ResultsPost-test results showed a significant reduction in body fat percentage for the high-intensity group compared with the low-intensity (p = 0.035) and control groups (p = 0.026). Significant reductions in energy and protein intake for the moderate-intensity group compared to the low-intensity (both p < 0.022) and control groups (both p < 0.007). In the high-intensity group, energy intake was significantly reduced compared to the control group (p < 0.001). Fat intake decreased in the moderate-intensity group compared to the high-intensity (p = 0.017) and control groups (p = 0.002). Carbohydrate intake was significantly lower in the moderate-intensity group compared to the control group (p = 0.001), while in the high-intensity group compared with the low-intensity (p = 0.049) and control groups (p < 0.001). The correlation between changes in body composition and nutritional intake was positive in the high-intensity group (r = 0.513–0.839, all p < 0.05) but negative in the control group (r = −0.606–−0.838, all p < 0.01).DiscussionThese findings suggest that high-intensity resistance training is most effective for improving body composition; both moderate- (especially) and high-intensity resistance training are the most influential in modifying nutritional intake; and high-intensity resistance training demonstrates the best correlation between changes in body composition and nutritional intake. Further research is required to address the contradictory result regarding body fat percentage compared to before, as well as to explore limitations related to population diversity, alternative exercise comparisons, rigorous dietary assessment methods, and underlying mechanisms.Systematic review registrationClinicalTrials.gov, NCT05530629.